On the Theory of Foreign Exchange Reserve Requirements - Archibald, G. C.; Richmond, J. (Review of Economic Studies, 1971)
G. C. Archibald, J. Richmond; On the Theory of Foreign Exchange Reserve Requirements12, The Review of Economic Studies, Volume 38, Issue 2, 1 April 1971, P